Explore New Low-carbon Travel Routes for Beijing Residents - Hu, Hongchang; Li, Xianghong (International Journal of Social Sciences and Public Administration, 2024)
This paper breaks the traditional thinking, re-examines the "supply and demand" relationship of transportation travel, and proposes to find a new path of low-carbon travel from the "demand side". The author innovatively proposed and demonstrated the "differentiated OAO office mode", and put forward personalized suggestions for the four travel needs of school, travel, medical treatment and commuting.